Randomised phase II study of panitumumab plus irinotecan versus cetuximab plus irinotecan in patients with KRAS wild-type metastatic colorectal cancer refractory to fluoropyrimidine, irinotecan and oxaliplatin (WJOG 6510G). (August 2020) - Sakai, Daisuke; Taniguchi, Hiroya; Sugimoto, Naotoshi; Tamura, Takao; Nishina, Tomohiro; Hara, Hiroki; Esaki, Taito; Denda, Tadamichi; Sakamoto, Takeshi; Okuda, Hiroyuki; Satoh, Taroh; Tsushima, Takahiro; et al.
Abstract: Background: Cetuximab has been shown to be clinically active when given in combination with irinotecan in patients with irinotecan-refractory metastatic colorectal cancer (mCRC). However, it has remained unclear whether panitumumab is effective when combined with irinotecan. We compared efficacies of both regimens in this randomised phase II study. Patients and methods: Patients with wild-type KRAS exon 2 mCRC previously treated with fluorouracil-, oxaliplatin- and irinotecan-based chemotherapies were randomised (1:1) to either panitumumab plus irinotecan (panitumumab arm) or cetuximab plus irinotecan (cetuximab arm). The primary end-point was progression-free survival (PFS). The planned sample size was 120, expecting a hazard ratio (HR) of 1.0 with non-inferiority margin of 1.3 (one-sided alpha error 0.2 and power 0.7). Major secondary end-points were overall survival (OS), response rate and safety. Results: From December 2011 to September 2014, 121 patients were enrolled, and 61 and 59 patients were randomised to the panitumumab and cetuximab arms, respectively (1 patient excluded). Most patients (97%) had received prior chemotherapies containing bevacizumab. The median PFS was 5.42 months in the panitumumab arm and 4.27 months in the cetuximab arm (HR = 0.64, 95% confidence interval [CI] = 0.44–0.94, P < 0.001 for non-inferiority, P = 0.058 for superiority), and median OS was 14.85 and 11.53 months (HR = 0.66, 95% CI = 0.44–1.00, P = 0.050 for superiority), respectively. The incidence of grade 3 or 4 hypomagnesaemia was higher in the panitumumab arm than that in the cetuximab arm (17% vs. 7%). Conclusion: Panitumumab may be non-inferior to cetuximab in combination with irinotecan in survival of patients with irinotecan-refractory mCRC. Highlights: Panitumumab may be non-inferior to cetuximab, with irinotecan for metastatic colorectal cancer. Favourable survival were shown in the panitumumab arm especially in subgroup after bevacizumab. Hypomagnesemia was higher in the panitumumab arm.